Analisis Kelayakan Investasi Usaha Peternakan Ayam Guna Memenuhi Kebutuhan Telur di UD. Hadhita Jaya Makmur - Afied, Putra Mahendra; Murnawan, Herry (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Feasibility Analysis of Investing in a Chicken Farming Business to Meet the Need for Eggs which aims to determine the feasibility of a business. In an analysis of the feasibility of establishing a business, it can be carried out through several aspects, namely a monetary perspective, a special perspective, a market perspective using several methods, namely Draft Budget (RAB), Net Present Value (NPV), Net Benefit Ratio (NET B/C ) Internal Rate of Return (IRR), Payback Period (PP) and). This analysis produces data that shows the RAB of the feasibility of UD's business investment. Hadhita Jaya Makmur amounting to Rp. 1,470,669,000, with an NPV of Rp. 347,561,231 IRR is 43%, then the business PP is for 2 years, and the NET B/C is 3. According to the existing analysis regarding feasibility here it can be concluded that investment in the UD.Hadita Jaya Makmur business has met the feasibility of business investment, because has a positive NPV value, higher IRR on funding costs, relatively short PP, and larger NET B/C and is financially profitable for this business.